Transient spaces and migrant workers : a case study of Golden Mile Complex. - Quek, Clive Yuen Kiat. (2010)
The development of a global market economy due to the process of globalization paves the way for large-scale labour migration. The temporary migration of these migrant workers leads to the formation of new spaces, which I assign the term, transient spaces, due to nature of people who gather there, i.e. the short term transient workers. These new ethnic enclaves provide a place where migrant workers can call them own, as they face difficulties assimilating into the host societies. Nostalgic memories of their hometown allow elements of their countries of origins to be recreated in these transient spaces in the form of consumer products, food, services, cultural goods, and their socialization process. Using Golden Mile Complex as a case study, this paper shows that various factors such as marginalized status of foreign workers, language barriers and economic constraints which lead to the gathering of Thai migrant workers at the complex.